A description of growth, carcass and reproductive traits of Sabi sheep in Zimbabwe - Matika, O.; Wyk, J.B. van; Erasmus, G.J.; Baker, R.L. (Elsevier, 2003)
A total of 4355 lamb and 4299 ewe records, obtained from Sabi sheep of Zimbabwe from 1984 to 1994, were analysed to describe growth, carcass and reproductive traits and to investigate non-genetic factors influencing their expression. Year of birth, sex, birth/rearing status of lamb, dam age, age of lamb and slaughter age were significant sources of variation for body weights, average daily gain, carcass and reproductive traits except for age (P>0.05) of lamb at 18 months of age, and ewe age for hot and cold carcass weight (HCW and CCW). Significant (P<0.001) two-way interactions were found between year of birth and sex for pre-weaning average daily gain, 12- and 18-month weight and for birth status and sex for lamb survival. Least squares means for body, carcass, ewe weights (kg) and average daily gains (g per day) were: 2.63 for birth weight (BW); 17.2 for weaning weight (WW) (recorded at 120 days of age); 23.5 for 12-month weight (12W); 35.7 for 18-month weight (18W); 124 for average daily gain between birth and weaning; 21.7 for total litter weaned; 14.6 for Kleiber ratio. Slaughter weights were low (29 kg) yielding 13.6 and 13.1 kg hot and cold carcass weights, respectively. Average weight of ewe at mating in May/June were 38 kg, and 35.6 kg for post-partum in October/November and 26.2 kg at weaning in February. The least squares means for reproductive traits were: 0.86, 1.01, 1.17, 0.83, 0.85 for ewes lambing to those exposed; lambs born to ewes exposed; lambs born to ewes lambing; lambs weaned to ewes exposed to the ram and lamb survival to weaning, respectively. The model best describing the data was constructed and discussed.